Effectiveness of school-based brief cognitive behavioral therapy with mindfulness in improving the mental health of adolescents in a Japanese school setting: A preliminary study - Kato, Kiun; Matsumoto, Yuki; Hirano, Yoshiyuki (Frontiers in Psychology, 2022)
Background Emotional regulation is important for adolescents’ adaptive development. Preventive interventions for anxiety and depression are necessary for reducing the development of disorders later in life, and emotional regulation is a potentially relevant factor. Objective We investigated the effects of a mindfulness-based psychological education and prevention program [the Mindfulness and Awareness Program (MAP)] on the mental health of junior high school students in Japan. Methods Our MAP primarily focused on mindfulness meditation to improve emotional regulation, thereby reducing depression and anxiety. The MAP comprised eight sessions (20 min each) administered by a school counselor in a school setting. All participants (N = 349) were 12–13-year-old adolescents from nine classes in two Japanese schools. The program was provided to the intervention group, wherein students were educated on emotional expression, emotional cognition, and emotional regulation. The control group received regular school counseling services. Results Compared with the control group, the intervention group showed significant improvement in emotional regulation and a decrease in depression and generalized anxiety. The effect was greater at the follow-up assessment than at the immediate post-intervention assessment, and greater in female students. Conclusion Our mental health prevention program exhibited efficacy in reducing depression and anxiety and enhancing emotional regulation in early adolescence. Further, it appeared to be more effective for female adolescents.